Diagnostic capabilities of non-treponemal and treponemal reactions in the early forms of syphilis. - Zakharov, S. V. (Medicni Perspektivi, 2017)
A comparative analysis of the sensitivity and specificity of immunoblotting against other non-treponemal and treponemal reactions was carried out in 215 patients with early forms of syphilis. A high diagnostic efficiency of immunoblotting in patients with early latent syphilis was established. It was found that only in case of primary syphilis, immunoblotting is inferior to Immunofluorescence reaction; this test can be used for differential diagnosis between hidden syphilis and false positive reactions to syphilis.